2021
DOI: 10.1038/s41598-021-90154-1
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-derived cardiovascular disease-related microRNAs elevated with prolonged sitting pattern among postmenopausal women

Abstract: Time spent sitting is positively correlated with endothelial dysfunction and cardiovascular disease risk. The underlying molecular mechanisms are unknown. MicroRNAs contained in extracellular vesicles (EVs) reflect cell/tissue status and mediate intercellular communication. We explored the association between sitting patterns and microRNAs isolated from endothelial cell (EC)-derived EVs. Using extant actigraphy based sitting behavior data on a cohort of 518 postmenopausal overweight/obese women, we grouped the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…These modifications are important for protein conformation and developmental processes [ 29 , 30 ]. Additionally, O-glycan are required for normal nervous system development and function [ 31 , 32 ], as well as cell-cell communication [ 33 , 34 ]. Given these roles, we investigated the impact of PGANT3 on the hematophagous behavior of Ae.…”
Section: Resultsmentioning
confidence: 99%
“…These modifications are important for protein conformation and developmental processes [ 29 , 30 ]. Additionally, O-glycan are required for normal nervous system development and function [ 31 , 32 ], as well as cell-cell communication [ 33 , 34 ]. Given these roles, we investigated the impact of PGANT3 on the hematophagous behavior of Ae.…”
Section: Resultsmentioning
confidence: 99%
“…miRNAs have been linked to endothelial cell dysfunction (Zheng et al 2021 ; Chang et al 2021 ). We have been interested in the molecular mechanisms regulating endothelial cell dysfunction after hemorrhagic shock (Wu et al 2021 ; Chipman et al 2021 ) and identified miR-19b as a key molecule (Wu et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%